Cooperative federalism in South Asia and Europe: Contemporary issues and trends - Vinod, M. J.; Joseph, Stefy V.; Chennatuserry, Joseph Chacko; Chryssochoou, Dimitris N. (Abingdon, Oxon ; New York, USA : Routledge, 2024)
"This book explores the challenges, opportunities, and trends impacting the working of federations in South Asia and Europe. It deliberates on the changing socio-economic realities, challenges facing the existing structures of governance, degrees of consociationalism, and the growing aspirations of people in South Asia and Europe. Through case studies from Greece, Germany, Austria, Switzerland, Spain, France, Sri Lanka, Pakistan, Nepal, Maldives, Bhutan, and India, the volume focuses on critical issues relating to cooperative federalism - its complexities, institutional dilemmas, and trends in South Asia and Europe. It discusses a variety of themes, including federal-state relations; cooperative governance; constitution; multiculturalism, fiscal relations, democratization, devolution of powers, consociationalism, and global citizenship to analyse the complexities of the existing federal polities in South Asia and Europe. It further emphasizes the need to strike a balance between the federal government and the constituent units in these regions. Topical and lucid, this book will be of interest to teachers, scholars, and researchers of political science, comparative government and politics, federalism, South Asian politics, European politics, governance studies, and political studies"--
European 'syspondia' : theorizing a late-modern political aggregate / Dimitris N. Chryssochoou -- Cooperative federalism in the United States through a conceptual lens / John Kincaid -- Federalism and democracy : the need for a differentiated approach / Patricia Popelier -- Fortunes of federating units in India / Krishna K. Tummala -- Civil society and cooperative federalism in India : the need for a conceptual enquiry / G. Gopa Kumar -- Emerging trends in Indian federalism : collaboration, competition and coordination / Sandeep Shastri and Katyayani Singh -- The federal dynamics of Indian foreign policy : issues, concerns and trends / MJ Vinod, Lakshmi Karlekar and Joseph Chacko Chennatuserry -- COVID-19 and its impacts on cooperative federalism in Austria / Peter Bussjäger and Mathias Eller -- The political economy of cooperative federalism and the implementation of cooperative federalism in Germany / Roland Sturm -- Federalism and power-sharing as modes of diversity management in Europe / Soeren Keil -- Executive absolutism and decentralized governance : a study of the Sri Lankan provincial council system / Upul Abeyrathne and Sumudu Walakuluge -- Cooperative federalism in Nepal : practice and prospects / Thaneshwar Bhusal -- Cooperative federalism in a multinational country : examining the case of Pakistan / Stefy V Joseph and Jairam R Prabhu.
Includes bibliographical references and index.
Keywords: Central-local government relations -- South Asia; History - South Asia; Central-local government relations -- Europe; Intergovernmental cooperation -- South Asia; Intergovernmental cooperation -- Europe; Decentralization in government -- South Asia; Decentralization in government -- Europe; Federal government -- South Asia; Federal government -- Europe